Dehydrocostus Lactone Attenuates the Senescence of Nucleus Pulposus Cells and Ameliorates Intervertebral Disc Degeneration via Inhibition of STING-TBK1/NF-κB and MAPK Signaling - Chen, Zhiqian; Yang, Xiao; Zhou, Yifan; Liang, Zhihao; Chen, Chen; Han, Chen; Cao, Xiankun; He, Wenxin; Zhang, Kai; Qin, An; Zhou, Tangjun; Zhao, Jie (Frontiers in Pharmacology, 2021)
The progression of intervertebral disc degeneration (IDD) is multifactorial with the senescence of nucleus pulposus (NP) cells and closely related to inflammation in NP cells. Dehydrocostus lactone (DHE) is a natural sesquiterpene lactone isolated from medicinal plants that has anti-inflammatory properties. Thus, DHE may have a therapeutic effect on the progression of IDD. In this study, NP cells were used to determine the appropriate concentration of DHE in vitro. The role of DHE in tumor necrosis factor-α (TNF-α)–induced activation of inflammatory signaling pathways and cellular senescence, together with anabolism and catabolism of extracellular matrix (ECM) in NP cells, was examined in vitro. The therapeutic effect of DHE in vivo was determined using a spinal instability model of IDD in mice. The TNF-α–induced ECM degradation and the senescence of NP cells were partially attenuated by DHE. Mechanically, DHE inhibited the activation of NF-κB and MAPK inflammatory signaling pathways and ameliorated the senescence of NP cells caused by the activation of STING-TBK1/NF-κB signaling induced by TNF-α. Furthermore, a spinal instability model in mice demonstrated that DHE treatment could ameliorate progression of IDD. Together, our findings indicate that DHE can alleviate IDD changes and has a potential therapeutic function for the treatment of IDD.